Adaptation of Dark Elf’s Fashion Style to Evening Party Dress - Kamaliyyah, Nadiyah Ayu; Astuti, Astuti; Sakti, Asri Wibawa (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
The aim of writing this scientific article is to adapt the Dark Elf fashion style to be an evening party dress. Dark Elf is a Norse mythological creature famous for its skills in war through its fashion style. Multi-layered dark purple attire, body armor made of iron alloy with some carvings, attire decorations resembling spider webs, and head accessories made of metal alloy depict that Dark Elf fashion style not only prioritizes functions and strategies but also pays attention to aesthetics. Dark Elf fashion style can be a source of ideas for an evening party dress. This study used the Gustami method. The Gustami method was applied to create works of art, and it is divided into three stages. The first is exploration, searching for source ideas ideally, and reviewing references. The second is design, creating a mood board and design, as well as visualizing the concept through the prototype. The third is embodiment, which is realizing and evaluating work. The realized was a dark purple party attire, which consisted of a bustier, an inner blouse, asymmetrical peplum adorned with silver garniture, a cloak variation, and a full-circle skirt made of layered tulle. The attire was worn with a turban as a head covering and the placement of a headpiece. Based on the validation test from the academic and practitioner assessment, the results showed that the adaptation of the Dark Elf fashion style for evening party dress has a percentage of 78%, which is valid from the adaptation process to the realization process of the dress.